COMPARATIVE ANALYSIS OF SURGICAL OUTCOMES IN AO-OTA 31-A2 FRACTURES: TWO-HOLE VS. FOUR-HOLE DYNAMIC HIP SCREW - Mesanovic, Edin; Fajic, Fikret; Mesanovic, Mirza (Sanamed, 2025)
Background: The choice of implant for the treatment of multifragmentary pertrochanteric fractures AO-OTA 31-A2 is complex, and the dynamic hip screw (DHS) can be used as a biomechanically safe and cost-effective option. Surgeons typically choose between DHS plates with two or four holes. The primary aim of this study was to determine whether there is a difference in surgery time, hospital stay, intraoperative blood loss, and incision length in patients with AO-OTA 31-A2 fractures treated with two-hole or four-hole DHS. The secondary aim was to compare the rate of complications, including fracture nonunion, implant breakage (DHS plate, sliding screw, compression screw, or cortical screws), cut-out, fracture collapse, and avascular necrosis. Methods: This retrospective study included 94 patients with AO-OTA 31-A2 fractures treated with DHS implants containing either two or four holes. Patients were divided into two groups: Group A, which included 60 patients treated with a two-hole DHS plate, and Group B, which included 34 patients treated with a four-hole DHS plate. Results: Group A had a significantly shorter surgery time (44.80± 8.01 minutes) compared to Group B (48.12 ± 5.43 minutes; p<0.05). Group A also had a significantly smaller incision (p<0.05). There were no significant differences between the two groups in terms of the remaining outcomes. Conclusion: The absence of significant differences in complication rates supports the conclusion that both DHS types are viable options for the treatment of AO-OTA 31-A2 fractures.